2020
DOI: 10.1039/d0ra01351j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of cobalt sulfide@reduced graphene oxide nanocomposites with outstanding electrochemical behavior for lithium-ion batteries

Abstract: Cobalt sulfide@reduced graphene oxide nanocomposites obtained through a dipping and hydrothermal process, exhibit ascendant lithium-ion storage properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…Determination of Mn and Co is stymied somewhat by multiple splitting caused by paramagnetic interactions with unpaired d-electrons during photoemission, which is a facet that complicates the analysis of 2p photoelectron spectra from first row transition metals in general . The position of the Mn 2p 3/2 peak at 641.2 eV is as expected comparing to literature on MnS and similarly the principle peak for Co 2p 3/2 at 778.2 eV for cobalt sulfide . However, other peaks are also evident (e.g., some structure in Co 2p 3/2 has a peak at 780.7 eV) again indicating a small amount of oxidation or potentially sulfate …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Determination of Mn and Co is stymied somewhat by multiple splitting caused by paramagnetic interactions with unpaired d-electrons during photoemission, which is a facet that complicates the analysis of 2p photoelectron spectra from first row transition metals in general . The position of the Mn 2p 3/2 peak at 641.2 eV is as expected comparing to literature on MnS and similarly the principle peak for Co 2p 3/2 at 778.2 eV for cobalt sulfide . However, other peaks are also evident (e.g., some structure in Co 2p 3/2 has a peak at 780.7 eV) again indicating a small amount of oxidation or potentially sulfate …”
Section: Resultssupporting
confidence: 87%
“…40 The position of the Mn 2p 3/2 peak at 641.2 eV is as expected comparing to literature on MnS 41 and similarly the principle peak for Co 2p 3/2 at 778.2 eV for cobalt sulfide. 42 However, other peaks are also evident (e.g., some structure in Co 2p 3/2 has a peak at 780.7 eV) again indicating a small amount of oxidation or potentially sulfate. 42 The S 2p spectrum requires three chemical species (each a spin−orbit split doublet) in order to adequately fit the data, with S 2p 3/2 binding energies of 161.3 (60% of the total intensity), 163.8 (31%), and 168.1 eV (9%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…54 However, for Figure 4d, the high loading of CoS nanoparticles (30%) may minimize the aggregation of carbon nanotubes in the crystalline matrix, which explains the attenuation of the peak intensity at 26°. 55 The XRD spectra further confirm growth of CoS on MWCNTs in the composites. 40,56 The presence of the C−S chemical bond suggested that CoS interacts strongly with MWCNTs.…”
Section: Resultsmentioning
confidence: 64%
“…The low peak intensity of (002) carbon of 10% CoS@MWCNTs (Figure a) may be attributed to the orientation of carbon nanotubes . However, for Figure d, the high loading of CoS nanoparticles (30%) may minimize the aggregation of carbon nanotubes in the crystalline matrix, which explains the attenuation of the peak intensity at 26° . The XRD spectra further confirm growth of CoS on MWCNTs in the composites.…”
Section: Resultsmentioning
confidence: 77%
“…13 It is seen that the increasing S-content gives a lead to increase in the capacity of the Li-ion cells. Although the cobalt sulfides have a better theoretical capacity than that of the graphite, 14 the main problem of these materials for Li-ion cells is the volume effect, resulting in poor cycle performance and showing the high capacity fade. To minimize this volume effect, researchers have found a solution to modify TMSs.…”
Section: Introductionmentioning
confidence: 99%